PENGENDALIAN DAN PENINGKATAN KUALITAS HIDUP PENDERITA LEPRA BERBASIS TEKNOLOGI MOLEKULER DI UNIT UJI TROPICAL DISEASE DIAGNOSTIC CENTRE UNIVERSITAS AIRLANGGA - Aksono, Bimo (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2010)
The aim of community service activities through a U-UJI TDDC will be conducted strain mapping M. leprae (genetic mapping) and TTC-based maping region mutation patterns of drug rifampin rpoB gene-based regions. The be- nefits of this activity is an increase in quality of life for the leprosy both socially and economically because of the application of molecular technology could help  early  detection  of  regional-based  Variable  Number  Tandem  Repeat (VNTR) of the TTC and rifampin-resistant gene (rpoB gene) and is expected to occur later therapeutic action will accelerate the decline in the incidence and cure the patient. Materials in this study isolates M. leprae from skin incision swabs, nasal mucosa and skin lesions biopisi of leprosy who come from a few enclaves leprosy in  Sumberaji-Lamongan District.  Criteria  for  patient  sample  is  still relatively new or are in treatment. Based on these criteria finally set 17 sample patients, whether included Pseudobasiler type (1 sample) and Multibasiler (16 samples). The method used is a nested PCR using specific primers from the region of the TTC, LP and rpoB. The results of nucleotide sequencing of both the sequence of the region of TTC, LP and rpoB region using GENETIX Mac software ver. 9.0. Community service activities based on the application of molecular technology by U-Uji TDDC, Airlangga University in endemic areas, especially infectious diseases in leprosy Sumberaji Lamongan District, from the results of PCR and nucleotide sequence analysis of a sample selected patients  indicates that the bacteria M. leprae in Sumberaji consists of three strains of M. leprae based on TTC-15, TTC-23 and TTC-28, while the analysis of the rpoB region of the mutation was not found either in CAG513-Gln, GAT516-Asp, CAC526- His, and TCG531-Ser-Leu CTG533, this indicates that the isolates of   M . leprae found in the leprosy in Sumberaji Lamongan district are sensitive to rifampin treatment. The results of this mapping can be used as a reference that rifampin  treatment  can  be used  for  therapy MDT  on  leprosy in  Sumberaji Lamongan district